Flowering Phenology Shifts in Response to Functional Traits, Growth Form, and Phylogeny of Woody Species in a Desert Area - Wang, Yan; Yang, Xiao-Dong; Ali, Arshad; Lv, Guang-Hui; Long, Yan-Xin; Wang, Ya-Yun; Ma, Yong-Gang; Xu, Chang-Chun (Frontiers in Plant Science, 2020)
Climatic factors are considered the major driving forces for variation of flowering phenology among species. Yet, whether flowering phenology of woody species varies with functional traits, growth form, and phylogeny in arid regions is unknown. In the present study, we evaluated the relationships of three characteristics of flowering phenology (i.e., first flowering date, end of flowering date, and flowering duration) against functional traits, growth form, and phylogeny across 59 woody plant species across three years in Urumqi city of the Xinjiang Autonomous Region, in Northwest China. The results showed that, plant functional traits and growth form had significant influences on the variability of flowering phenology among species. The contributions of fruit type (34.7-43.5%) and flower color (30.1-30.7%) to the variability of flowering phenology were larger than those of pollination mode (4.6-14.4%), life form (8.4-14%) and maximum plant height (9.7-13.1%).Trees had the significant correlations in terms of flowering duration against first flowering date and end of flowering date, while shrubs showed the opposite pattern. The values of phylogenetic signal (Blomberg’s K) of the three characteristics of flowering phenology ranged from 0.36 to 0.43, which were significantly lower than the expectation of the Brownian motion model. Our results suggested that functional traits, growth form and phylogeny all affected variability of flowering phenology among species. Our results provide a new perspective for correctly evaluating the relationship between global climate change and plant reproduction.